Factors influencing business model innovation of Chinese SMEs: A conceptual study - Li Haibo; Noor Fzlinda Fabeil (Universal Publishers, 2024)
Purpose: The main objective of this paper is to study the key factors affecting the implementation of BMI in China. Design/methodology/approach: This study is based solely on secondary sources, examples including academic papers, journal articles, books, and websites, to further investigate the concept. Findings: Key factors influencing BMI among Chinese SMEs include relational resources, digital technology and the long tail, the study found. Research implications: The conclusions of this study combine the specific circumstances of the current external environment of Chinese SMEs and make innovative and complementary contributions to the conceptual research on the factors influencing BMI. Practical implications: Changes in the external environment make it extremely difficult for SMEs to successfully implement BMI. To improve the success rate of BMI, SMEs must first clearly understand the factors influencing BMI, and then take targeted actions. Originality/value: This paper presents a new conceptual study in the context of reality, explaining three key influences that affect business model innovation in Chinese SMEs, namely relational resources, digital technology and the long tail. It also proposes to measure BMI in terms of the dimensions of the five major activities of a business model, with a total of 18 relevant hypotheses.